Building a sustainable institutional model for ornamental fish farming export villages in Indonesia - Andiga Dompak B. Tarihoran; Musa Hubeis; Siti Jahroh; Nimmi Zulbainarni (International Journal of Agricultural Sustainability, 2024)
Despite its great fisheries biodiversity, Indonesia is not the world's largest ornamental fish exporter. To improve export competitiveness, it is also necessary to strengthen the cluster competitiveness through institutional development. Indonesia contains several ornamental fish-producing regions, and the government has designated several aquaculture farming villages, including four regions for ornamental fish farming. This research aims to build a sustainable institutional model of an ornamental fish farming export village (OFFEV) that is expected to increase Indonesia's ornamental fish exports. The study utilized the Interpretive Structural Modeling (ISM) methodology. This approach aims to ascertain the hierarchical prioritization of stakeholders and the requisite programme stages for achieving the success of the OFFEV initiative. Through identification, judgment, and validation from 18 experts who participated in the study, the results reveal that the fisheries department, Ministry of Marine Affairs and Fisheries, trade attachés, customs, and research institutions can drive the OFFEV. Short-term programmes are the main priorities, including sustainable cultivation and quarantine assistance, cooperative establishment, facilities and infrastructure support, broodstock aid, funding, product marketing training, and partnership programmes. Finally, based on the ISM results and expert opinion, we built an OFFEV model centred on export-oriented Village-Owned Enterprises or multi-party cooperatives.